2003
DOI: 10.1128/iai.71.12.6850-6856.2003
|View full text |Cite
|
Sign up to set email alerts
|

An Enzymatically Active A Domain Is Required for Cholera-Like Enterotoxins To Induce a Long-Lived Blockade on the Induction of Oral Tolerance: New Method for Screening Mucosal Adjuvants

Abstract: The cholera-like enterotoxins (CLETS), cholera toxin (CT) and Escherichia coli heat-labile toxin (LT), are powerful mucosal adjuvants. Here we show that these toxins also induce a long-lived blockade (of at least 6 months) on the induction of oral tolerance when they are coadministered with the antigen ovalbumin. Strikingly, only enzymatically active CLETS induced this blockade on the induction of oral tolerance. In this regard, the enzymatically inactive mutants of CT and LT, CTK63 and LTK63, and their recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In support of this, CT and the related toxins Escherichia coli heat-labile enterotoxin and pertussis toxin were found to induce the maturation of DC (2,3,21). With further study, the elevated cAMP levels induced by these toxins were found to be responsible for DC maturation (2, 3), and their enzymatic activity has been shown to play a dominant role in adjuvanticity (5,6,23,34,37).Prostaglandins, most notably prostaglandin E 2 (PGE 2 ), have gained notoriety for their ability to synergize with other agonists to activate DC (42). Interestingly, CT has been shown to increase the production of PGE 2 in many cell types, including…”
mentioning
confidence: 84%
“…In support of this, CT and the related toxins Escherichia coli heat-labile enterotoxin and pertussis toxin were found to induce the maturation of DC (2,3,21). With further study, the elevated cAMP levels induced by these toxins were found to be responsible for DC maturation (2, 3), and their enzymatic activity has been shown to play a dominant role in adjuvanticity (5,6,23,34,37).Prostaglandins, most notably prostaglandin E 2 (PGE 2 ), have gained notoriety for their ability to synergize with other agonists to activate DC (42). Interestingly, CT has been shown to increase the production of PGE 2 in many cell types, including…”
mentioning
confidence: 84%
“…Spleens were mashed through 70-m-pore-size strainers in serum-free DMEMϩ10. Pelleted cells were resuspended in erythrocyte lysis buffer (144 mM NH 4 Cl, 17 mM Tris, pH 7.4, and Pen-Strep) and washed in serum-free DMEMϩ10. Splenocytes in PBS plus 5% BGS were incubated with 5 M carboxyfluorescein diacetate succinimidyl ester (CFSE; Molecular Probes, Eugene, OR) for 10 min at 37°C and washed after the reaction was quenched with 10 volumes of cold DMEMϩ10 (43).…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have reported that nontoxic CTB by itself can act as an antigen carrier and is highly immunostimulatory (17,27,47). The ability of nontoxic CTB to effectively block oral tolerance in the absence of enzymatic activity from CTA remains controversial, however, and toxigenic CT is clearly a potent adjuvant even in the absence of CTB (1,4,38). Toxigenic CT however is unsuitable for use in humans, and thus there has been much effort to separate the toxigenicity and adjuvanticity of this molecule.…”
mentioning
confidence: 99%
“…In the latter role it has been described as an apoptoic cell pattern recognition receptor' and could help terminate proinflammatory responses through activating antiinflammatory pathways [130]. Antiinflammatory macrophage phenotypes are already known to be induced by some microbial-related ligands, including the receptor-binding B unit of cholera toxin [131][132][133], the similar non-toxic AB complex of E. coli [134] excretory/secretory material from live adult filarial parasites [135][136][137] and Gram-negative flagellin [138]. Both extracellular and intracellular infections may elicit innate tolerance.…”
Section: Innate Tolerance: Receptors Responses and Mechanismsmentioning
confidence: 99%